AI Based Online Verification of Scheme Beneficiary - Velgekar, Vibhuti; Sawant, Shreya; Gawade, Samiksha; Jose, Basil; Bhogan, Snehal; Naik, Gaurav; Shirgaonkar, Vishvesh (International Journal of Computer Sciences and Engineering, 2021)
In order to benefit from different social schemes, the beneficiaries need to submit his/her Life Certificate in offline or online modes which are not affordable by the common man. This certificate is used as a proof to ensure that the person mentioned in the ‘Life Certificate’ is alive. The current prevailing methods for this are time-consuming as well as tedious for senior citizens as the have to stand in long queues. This paper presents a computationally simple and efficient enhancement technique that uses voice-verification algorithms to distinguish the beneficiaries and perform verification. The proposed method uses online mode along with feature extraction and pattern matching techniques.